2013
DOI: 10.1089/ars.2012.4577
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disulfide Isomerase Modification and Inhibition Contribute to ER Stress and Apoptosis Induced by Oxidized Low Density Lipoproteins

Abstract: PDI modification by oxLDLs or by reactive carbonyls inhibits its enzymatic activity and potentiates both ER stress and apoptosis by oxLDLs. PDI modification by lipid peroxidation products in atherosclerotic lesions suggests that a loss of function of PDI may occur in vivo, and may contribute to local ER stress, apoptosis, and plaque progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 49 publications
5
60
0
1
Order By: Relevance
“…Mechanisms orchestrating this response deserve further investigation and may relate, at least in part, to the severe ER stress during vessel repair because sustained ER stress is often associated with increased PDI expression in several diseases, 12 including atherosclerosis. 28 Our data ( Figure 2) as well as recent studies from our group (T. Araujo et al, unpublished data, 2015) suggest that pecPDI levels directly correlate with total PDI expression. This is consistent with the correlations between total PDI and vessel remodeling observed in human specimens (Figure 1).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Mechanisms orchestrating this response deserve further investigation and may relate, at least in part, to the severe ER stress during vessel repair because sustained ER stress is often associated with increased PDI expression in several diseases, 12 including atherosclerosis. 28 Our data ( Figure 2) as well as recent studies from our group (T. Araujo et al, unpublished data, 2015) suggest that pecPDI levels directly correlate with total PDI expression. This is consistent with the correlations between total PDI and vessel remodeling observed in human specimens (Figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…Previously reported vasculoprotective effects of PDI focused mainly on prosurvival intracellular PDI effects in ER dysfunction associated with oxidized lipids 28 and hypoxia. 29 Our data add to other specific effects of pecPDI pool, which include immune reactions, 16 pathogen response, 16,27 and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…109 These adducted proteins directly affect ER function, especially protein disulfide isomerase. 110 In support of this idea, it was shown that the folding of protein to allow optimal formation of disulfide bonds is highly redox-dependent in the ER. 111 Thus, the accumulation of misfolded proteins with HNE-adducts in ER could compromise cell survival.…”
Section: Hne: a Serial Killermentioning
confidence: 96%
“…Loss of PDIs activity has been associated with the pathogenesis of numerous disease states (6). In particular, PDI and PDIA3 prevent apoptotic cell death associated with ER stress and protein misfolding in various in vivo and in vitro models (7)(8)(9)(10)(11)(12)(13). The up-regulation of PDIA3 correlates with the accumulation of misfolded prion proteins and suppresses prion neurotoxicity (7), whereas reducing PDIA3 expression in cancer cells increases the apoptotic response to fenretinide (12).…”
Section: Protein Disulfide Isomerase (Pdi)mentioning
confidence: 99%